The impact of US trade sanctions on the global trade of target countries: Do the political institutions of the targets matter? - Sajjad Faraji Dizaji; Mohammad Reza Farzanegan (Philipps-University Marburg, School of Business and Economics, 2023)
We investigate the effects of US-imposed trade sanctions on the global trade patterns of sanctioned countries by employing a gravity model that incorporates data spanning from 1980 to 2020 across 79 nations and other various factors, this study explores how sanctions impact trade dynamics. The results reveal that both partial and complete US sanctions lead to significant reductions in bilateral trade between the US and target countries, with complete sanctions showing a more substantial negative impact. Moreover, while partial import sanctions and comprehensive import and export sanctions reduce third countries' exports to and imports from target countries, partial export sanctions reduce only third countries' imports without notably affecting total trade or third countries' exports to the sanctioned nations. Finally, we show that target countries with stronger political institutions, as measured by democracy indicators, manage to alleviate some of the adverse effects of US sanctions on bilateral trade with both the US and third countries.
Keywords: 330; Sanctions; Trade; Import; Export; Democracy; Political institutions; Gravity Model